Role of artificial intelligence in enhancing competency assessment and transforming curriculum in higher vocational education - Yan, Jingli; Tian, Haoheng; Sun, Xia; Song, Linjia (Frontiers in Education, 2025)
The study investigates the competency assessment outcome of AI-driven training, student engagement, and demographic factors. Previous studies have examined these factors individually, but this research integrates them to assess their combined impact on competency scores. Variables such as competency scores, AI-driven training, student engagement, gender, and vocational training levels were systematically collected following FAIR principles. Python libraries were used for cleaning and preprocessing the dataset; missing values were filled and outliers were handled using the Tukey method. The use of EDA further disclosed strong positive correlations with student engagement and competency scores resulting from AI-driven training. Nonetheless, since it is an observational study, these associations must not be taken to be causal. Inferential statistics - like t-tests and ANOVA - were established by gender and vocational training level. Machine learning algorithms were used to predict competency scores, and Random Forests showed the highest predictive power compared to linear regression (R2 = 0.68 vs. 0.41). This suggests the necessity of modeling non-linear relationships in competency prediction. Inferential statistics (ANOVA, t-tests) revealed gender and vocational training-level effects. Random Forests outperformed linear regression (R2 = 0.68 vs. 0.41), uncovering non-linear relationships. KMeans clustering revealed three student groups necessitating individualized interventions: Cluster 1 (high AI engagement/low competency) requires skill-building support; Cluster 2 (balanced engagement/competency) is served by ongoing adaptive training; and Cluster 3 (low engagement/high competency) requires engagement-fostering strategies. These results highlight the importance of AI-supported training and student interaction to improve competency attainment. These findings have practical implications for vocational education and training institutions by promoting personalized learning approaches that are responsive to the various needs of students. Ethical considerations of AI-based evaluation, including bias and fairness, are worthy of exploration.